(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The Indonesian nation is a pluralistic nation because its society consists of a collection of people or groups with ethnic characteristics that have various cultures with different ethnic backgrounds. One of the cultures found in Indonesia, especially the island of Java, is Gamelan. In traditional musical instruments Kenong can be associated with mathematical material. Based on Bishop’s analysis which consists of counting, locating, measuring, designing, playing, and explaining. So that the research problems that will be studied are: what is a traditional kenong musical instrument?; and what are the characteristics of the traditional Kenong musical instrument?. Furthermore, the results in this study include: understanding the traditional musical instrument kenong; and characteristics of traditional kenong musical instruments. The purpose of this study is to explore mathematical ideas contained in traditional Kenong musical instruments that can be used when learning mathematics at school.